Type designation of the Lamarck’s name Buxus balearica (Buxaceae) - Ferrer-Gallego, Pedro Pablo; Rosselló, Josep Antoni; Sáez, Llorenç (Phytotaxa, 2019)
The Lamarck’s name Buxus balearica is discussed and neotypified from a specimen preserved at MA collected in Mallorca (Balearic Islands, Spain). In addition, the lectotypes of B. longifolia and B. balearica f. granatensis, currently treated as two heterotypic synonyms of B. balearica, are designated from original material preserved at G-BOIS and MA, respectively